Adopsi E-commerce pada UMKM selama Masa Krisis: dengan Peran Mediator Kapabilitas Dinamis - Rossalina Christanti; Juan Chandra Jatiputra (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to investigate the effect of e-commerce adoption on cultural SMEs’ performance during the pandemic. While the e-commerce market is now highly developed in Indonesia, most global companies are focusing on bigger markets like Indonesia so every business in Indonesia is adapting their own business model to survive. Considering that this pandemic does not look at layers of society, the demand for agility to adapt does not only 'apply' to large-scale businesses but all sectors, including the SMEs. As the pandemic hits all types of organizations, this study also believes that SMEs’ dynamic capabilities would moderate the effect of e-commerce adoption on cultural SMEs’ performance. Furthermore, this study aims to examine the moderating effect of dynamic capabilities among cultural SMEs as an important dimension of business ability to deal with rapid environmental changes in the midst of a crisis. Quantitative data analysis was used to investigate research data. Questionnaires were distributed to 120 SMEs owners in the areas of Temanggung, Magelang, Yogyakarta and Solo in the cultural field. SPSS was used to analyze the relationship between variables. Result shows that the e-commerce adoption effect on business operations proved to affect cultural SMEs’ financial performance significantly. But, the influence of e-commerce adoption on marketing is not proven to significantly affect the financial performance of cultural SMEs. Meanwhile, dynamic capabilities construct was also proved to strengthen the effect of e-commerce adoption on business operations on cultural SMEs’ financial performance.